2020
DOI: 10.1186/s13071-020-3971-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of bovine cysticercosis in Brazil: current knowledge and way forward

Abstract: Background: Taenia saginata taeniosis/cysticercosis has been well studied in several countries. Brazil is one of the most important beef exporting countries and has one of the highest cattle population size in the world. In this country, bovine cysticercosis (BCC) remains the most frequent reported zoonosis detected during post-mortem inspection, resulting in costs for the beef sector and public health. We performed a systematic literature review regarding data about BCC epidemiology in Brazil and meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
0
6
0
5
Order By: Relevance
“…In a meta-analysis study, Rossi et al (2020) reported a reduction in the prevalence of cysticercosis over time in several Brazilian states. In general, a reduction in occurrence rates was observed over the years, which was more pronounced for cysticercosis than for hydatidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis study, Rossi et al (2020) reported a reduction in the prevalence of cysticercosis over time in several Brazilian states. In general, a reduction in occurrence rates was observed over the years, which was more pronounced for cysticercosis than for hydatidosis.…”
Section: Discussionmentioning
confidence: 99%
“…They can also spread through the air, rain or other climatic phenomena, contaminating water or food, which constitute a transmission route to cattle, the intermediate hosts (Thompson 2017). Infected cattle develop cysticercosis characterized by cysticerci at various anatomical sites (Rossi et al 2020), but preferably in skeletal or cardiac muscles (Marshall et al 2016). Echinococcus granulosus has a similar biological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de uma grande evolução para os estabelecimentos de abate de bovino, pois obriga uma maior proximidade do estabelecimento com o seu fornecedor de matéria-prima, possibilitando um maior controle dos produtores que resultam no abate de animais com maior prevalência de patologias e doenças infecciosas, incluindo as zoonóticas. Tais ações resultarão em um maior controle de áreas geográficas com maior prevalência de doenças específicas, como a cisticercose (ROSSI et al, 2020), além da diminuição de prejuízos econômicos frente às condenações oriundas da inspeção ante e post mortem e maior eficiência no controle sanitário dos produtos de origem animal.…”
Section: Da Responsabilização Dos Estabelecimentos Perante a Cadeia Primáriaunclassified
“…Esse parasita tem sido frequentemente relatado em países subdesenvolvidos e desenvolvidos de diferentes continentes, como nas Américas (BRAAE et al 2018), Ásia (EICHENBERGER et al 2020), África (SARATSIS et al 2019) e Europa (LARANJO-GONZÁLEZ et al 2016). No Brasil, essa zoonose é frequentemente detectada nos abatedourosfrigoríficos e a sua distribuição espacial varia entre as diferentes regiões do país, com uma maior ocorrência nas Regiões Sul e Sudeste (ROSSI et al, 2014;ROSSI et al 2020).…”
Section: Comunicaçãounclassified
“…Número Rossi et al (2017), entre os anos de 2010 a 2015, determinou-se uma prevalência de 0,62% no Brasil. Ambos os estudos trazem valores próximos ao encontrado nesse estudo, mas sabe-se que a ocorrência dessa enfermidade é variável nas diferentes regiões, estados e municípios brasileiros (ROSSI et al 2020) e que frequentemente valores superiores ao deste trabalho são reportados no Estado de São Paulo (FERREIRA et al 2014;COMIN et al 2021).…”
Section: Anounclassified